AB0857 Spontaneous Regression of Ebv-Associated Lymphoproliferative Disorder in A Juvenile Idiopathic Arthritis Patient after Discontinuation of Methotrexate and Etanercept. (15th July 2016) - Klein, A.; Reinhard, H.; Mueller, A.; Horneff, G.
Abstract : Background: The risk for malignancies especially lymphoma seems higher for JIA patients. So far, treatment with TNF-inhibitors, especially with Etanercept has not been described to further enhance the malignancy rate. The association of EBV induced lymphoproliferation/lymphoma has been described in adult patients with rheumatoid arthritis upon treatment with several immunosuppressive drugs including Methotrexate and may not be related to Etanercept. Results: A case of a 16-year-old female patient with polyarticular JIA since the age of 4 years is reported. The patient also suffers from a complex congenital cardiac and several other congenital abnormalities including mental retardation, sensoneurinal hearing loss, growth retardation and pubertas tarda. Microdeletion 22q was ruled out and a microarray assay in search of an underlying genetic disorder was normal. When diagnosed with JIA at the age of 4 years treatment with methotrexate was started but discontinued due to elevated liver enzymes 10 months later. At the age of 13 years, JIA relapsed with multiple joint involvement and treatment with methotrexate and Etanercept was initiated leading to acceptable clinical condition, with functional impairment due to restricted joint movements. Complete remission of JIA was not reached. After 3 years on combination treatment, the patient reported multiple subcutaneous nodules on the lower extremities. On palpation such nodules were 0.5 to 2.0 cm of size and the largest one was slightly tender. No overlying skin changes such as erythema were noted. Laboratory analysis revealed normal blood counts, normal CRP, but elevated lactate dehydrogenase and uric acid. Ultrasound investigation showed several round lesions with a maximum diameter of 1.7 cm with enhanced signal of capsules and in some of the lesions hypoechoic centers. Thoracic CT detected a mediastinal lesion suggestive of a mediastinal lymphoma. Biopsy of the largest nodule revealed diffuse large B-cell lymphoma (DLBCL). EBV-RNA (EBER-in-situ-hybridization) could be detected in the nuclei of the blasts. While IgG antibodies to EBV VCA and EBNA were positive, EBV VCA IgM was negative and in the patient's peripheral blood EBV DNA PCR gave negative results. The patient was classified as clinical stage IIIA due to a mediastinal lesion. Immunosuppressive treatment was discontinued immediately, which led to regression of remaining nodules, mediastinal lymphoma and normalization of lactate dehydrogenase. So far, no recurrence of DLBCL or JIA could be detected, 9 months after discontinutation of immunosuppressive treatment. Conclusions: The clinical course with spontaneous regression of the lymphoproliferative lesions and normalization of LDH after discontinuation of antirheumatic treatment lead to the assessment of the neoplasm as lymphoproliferative disorder (LDP) associated with iatrogenic immunosuppression rather than manifest lymphoma. The patient was considered to have iatrogenic lymphoproliferative disorder classified as "other iatrogenic immunodeficiency-associated lymphoproliferative disorders" by the WHO. This is the first case-report of a JIA patient with EBV-positive DLBCL following administration of Etanercept and Methotrexate showing spontaneous regression of lymphoproliferation after discontinuation of antirheumatic treatment. Disclosure of Interest: None declared